2016
DOI: 10.3390/horticulturae3010005
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Performance of Horticultural Substrates—1. Method for Measuring the Hydraulic Quality Indicators

Abstract: Besides nutrient composition, the hydraulic performance of horticultural substrates is a main issue for evaluating their quality for horticultural purposes. Their water and air capacity and their suitability for transporting water are important hydraulic quality indicators. Shrinkage and water repellency could have a negative impact on storing and transporting water and solutes. The commonly used methods and devices for quantifying the water retention properties of horticultural substrates (sand box, pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…3,6,25,36) and two substrates (33, 34) were peat-free. The Chrysal active substrate package (No. 8) provided no information about the ingredients.…”
Section: Horticultural Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6,25,36) and two substrates (33, 34) were peat-free. The Chrysal active substrate package (No. 8) provided no information about the ingredients.…”
Section: Horticultural Substratesmentioning
confidence: 99%
“…The water retention curve and the unsaturated hydraulic conductivity function were measured using the extended evaporation method (EEM) and the HYPROP system from saturation to close to the wilting point [7,8]. If hydraulic information in the dry range is not required, the measurement could be stopped at 100 hPa or at any other tension.…”
Section: Hydraulic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evapotranspiration rates depend on greenhouse environmental conditions, and are also affected by the water supply to the roots [91]. For scheduling irrigation, hydraulic properties and water content dependence on substrate suction must be known as they influence the water movement and retention in the substrate [91][92][93]. Water retention curves or moisture characteristic curves relate the water content in a specific substrate to the matric potential at a given tension or height [94].…”
Section: The Soil/substrate Physical Properties and The Irrigation Dosementioning
confidence: 99%
“…However, information to the hydraulic properties is missing of the substrate package. Until recently substrate buyers cannot draw any conclusions regarding the hydraulic properties on the basis of the declaration and the ingredients of the particular product he has bought, 1,[3][4][5] concluded that there is a lack of technologies and methods for the effective physical characterization and evaluation of substrate application in horticulture. The papers [3][4][5] are in the public domain.…”
Section: Introductionmentioning
confidence: 99%